1996
DOI: 10.1128/iai.64.2.466-471.1996
|View full text |Cite
|
Sign up to set email alerts
|

Elevated aspartic proteinase secretion and experimental pathogenicity of Candida albicans isolates from oral cavities of subjects infected with human immunodeficiency virus

Abstract: Isolates of Candida albicans from the oral cavities of subjects at different stages of human immunodeficiency virus (HIV) infection or uninfected controls were examined for (i) production of aspartic proteinase(s), a putative virulence-associated factor(s); (ii) the presence in the fungal genome of two major genes (SAP1 and SAP2) of the aspartic proteinase family; and (iii) experimental pathogenicity in a murine model of systemic infection. It was found that the fungal isolates from symptomatic patients secret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
72
2
3

Year Published

1999
1999
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(79 citation statements)
references
References 41 publications
(82 reference statements)
2
72
2
3
Order By: Relevance
“…We have then corroborated our hypothesis that this direct interaction may in part be responsible for the altered virulence of C. albicans in HIV-positive subjects [12] by demonstrating an augmentation of fungal virulence properties in vitro following HIV binding [16]. In particular, phagocytosis by polymorphonuclear leukocytes was decreased [16], whereas secretion of aspartic proteinases (Saps), one of the major virulence factors of C. albicans [17,18], produced to a higher extent by C. albicans isolates from HIV-positive individuals compared to isolates from uninfected subjects [19,20], was found to be increased after this interaction [16]. An involvement of Saps in gp41 binding itself, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…We have then corroborated our hypothesis that this direct interaction may in part be responsible for the altered virulence of C. albicans in HIV-positive subjects [12] by demonstrating an augmentation of fungal virulence properties in vitro following HIV binding [16]. In particular, phagocytosis by polymorphonuclear leukocytes was decreased [16], whereas secretion of aspartic proteinases (Saps), one of the major virulence factors of C. albicans [17,18], produced to a higher extent by C. albicans isolates from HIV-positive individuals compared to isolates from uninfected subjects [19,20], was found to be increased after this interaction [16]. An involvement of Saps in gp41 binding itself, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies carried out in Brazil showed that this activity was present in about 53% to 100% of Candida albicans cultures (13,14,19) . According to international data, proteinase activity was detected in 16% to 100% of the studied samples (2,3,6,8,12) . Our study did not find a correlation between in vitro proteolytic activity and the severity of the lesion.…”
mentioning
confidence: 99%
“…Virulence factors from C. albicans were shown to be more expressive in HIV-carrier individuals. 20,21 The frequency of oral candidiasis in HIV+ patients varies among the different reports, and can af-fect up to 94% of infected individuals. However, the prevalence of candidiasis in HIV+ individuals has diminished.…”
Section: Discussionmentioning
confidence: 99%